Pemodelan Loyalitas Konsumen Berdasarkan Kepuasan Terhadap Atribut Produk Madu Suhita - bina unteawati; Edy Humaidi; Kusmaria (Jurnal Penelitian Pertanian Terapan, 2022)
The purpose of this study is to analyze what factors affect consumer satisfaction with Suhita honey, analyze what factors affect consumer loyalty Suhita honey, analyze the effect of satisfaction on consumer loyalty Suhita honey, describe a model of consumer loyalty on product attributes of Suhita honey. This research was conducted by survey method and direct observation. The sampling method in this study will be carried out using the accidental sampling method. The analytical techniques used are descriptive analysis and Structural Equation Modeling (SEM) analysis. The results showed that only two variables had a significant effect, namely the product quality variable with P-values ​​of 0.033 (<0.05) and the service quality variable with P-values ​​of 0.031 (<0.05). Meanwhile, the price variable has no significant effect on consumer satisfaction, seen from the P-values ​​of 0.815 (> 0.05). Furthermore, for the test results whether there is an influence between consumer satisfaction on consumer loyalty shows a significant influence seen from the value with P-values ​​of 0.000 (<0.05), meaning that satisfaction has an effect on consumer loyalty.